2014
DOI: 10.1177/1534735414555809
|View full text |Cite
|
Sign up to set email alerts
|

The Responsiveness, Content Validity, and Convergent Validity of the Measure Yourself Concerns and Wellbeing (MYCaW) Patient-Reported Outcome Measure

Abstract: MYCaW scores were highly responsive to change, allowing personalized patient outcomes to be quantified; the qualitative coding framework appears generalizable across different integrative oncology settings and has broader coverage of patient-identified concerns compared with existing cancer-related patient-reported outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Moreover, we identified that ICs wanted to know how to obtain reliable information on lifestyle such as stress management and nutrition and relaxation techniques for themselves and the person they were caring for. This unmet need was also noted when developing the first MYCaW coding framework for people with cancer [ 34 ] and is a category that is not covered in the context of lifestyle changes in any of the outcome measures recently reviewed by Shilling et al [ 12 ]. Five outcome measures in the systematic review [ 12 ] ask people to rate levels of stress, and a further four refer to levels of distress, but this is a different context to ascertain whether people have reliable information to manage their stress levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we identified that ICs wanted to know how to obtain reliable information on lifestyle such as stress management and nutrition and relaxation techniques for themselves and the person they were caring for. This unmet need was also noted when developing the first MYCaW coding framework for people with cancer [ 34 ] and is a category that is not covered in the context of lifestyle changes in any of the outcome measures recently reviewed by Shilling et al [ 12 ]. Five outcome measures in the systematic review [ 12 ] ask people to rate levels of stress, and a further four refer to levels of distress, but this is a different context to ascertain whether people have reliable information to manage their stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…MYCaW is a validated patient-centred outcome measure that quickly captures all the concerns of people with cancer in a way that is not possible with a predetermined list of items [ 31 ]. Our previous research has comprehensively mapped the concerns and wellbeing of people with cancer internationally, using Measure Yourself Concerns and Wellbeing (MYCaW) [ 32 34 ]. This ensures that service users’ perspectives are represented in the routine data monitoring, evaluation and research [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measure has a broad coverage of patient identified-concerns, it is quick, acceptable, reliable, and gives some indication of clinically meaningful change [39][40][41]. However MYCaW is not in itself suitable as a quality of life measure [39], for this a conditionspecific assessment tool is needed. The lymphoedema quality of life scale (LYMQOL) was developed by healthcare professionals in consultation with service users; separate tools were developed for arm and leg lymphoedema.…”
Section: Discussionmentioning
confidence: 99%
“…It is quick to administer and acceptable to patients, practitioners and researchers [38]. It is highly responsive to change and captures a wider range of patient-identified concerns compared to similar outcome measures [39], and good inter-rater reliability (kappa 0.85) has been established for the qualitative analysis [40]. An analysis of work with similar 7-point scales suggests that a change of over 0.7-1.0 on MYCaW measurements is likely to be clinically significant [41].…”
Section: Data Collectionmentioning
confidence: 99%
“…General tools for capturing patient-reported outcomes and disease-specific tools are increasingly being used in other disease states [18][19][20]. These assessments aid in identifying disease burden or treatment effects that are most important or bothersome to the patient in everyday life.…”
Section: Outcome Goals Beyond Survival In Pediatric Heart Failure Andmentioning
confidence: 99%